Problems of improving the legal mechanism for consumer protection and prospects for development (Journal of actual problems of jurisprudence, 2021)
This article deals with the issue of protecting the rights of consumers when purchasing goods. Every member of society, from a small to large, is a consumer of goods, works, certain or other services and often faces a violation of consumer rights, so every citizen should know about their rights as a consumer and be able to protect themselves. This question is relevant. In his address to the people of Kazakhstan, published on October 5, 2018, the president of the Republic of Kazakhstan noted that the health of the nation is the main priority of the state. Almost every person is a consumer of goods, works and services throughout his life; he acts as a participant in the legal relations that have developed in the consumer market. At the same time, consumer rights are often violated. The consistent formation and further development of the foundations of civilized legal regulation of relations with the participation of consumers, which was supposed to be in the period of formation of market relations, the foundation of which appeared, made it possible to balance the interests of consumers in a timely manner with the interests of business and obtain a comprehensive basis of legal norms, proved its effectiveness and viability. In an unstable market economy, manufacturers often impose favorable conditions on consumers only for the purchase of goods and services. Key words: consumer, consumer rights, consumer protection, competition, safe goods.